Chemical Ecology of Insect Parasitoids 2013
DOI: 10.1002/9781118409589.ch8
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and its Effects on the Chemical Ecology of Insect Parasitoids

Abstract: Over the course of evolutionary time, insect parasitoids have developed diverse strategies for using chemical compounds to communicate with various protagonists within their environment (i.e. conspecifi cs, their hosts, and the plants on which their hosts are living). Unravelling the evolutionary meaning of such chemical communication networks not only provides new insights into the ecology of these insects but also contributes to improving the use of parasitoids for the control of insect pests in biological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 103 publications
0
11
0
3
Order By: Relevance
“…On the one hand, insects using CO 2 to detect their food source or oviposition site (such as moths, fruit flies or hematophagous insects) can be directly affected . On the other hand, as described before, altered leaf chemistry and temperature can affect second and higher trophic levels in all possible ways . For instance, in aphids, even a single clone has been reported to display different responses to high CO 2 content, depending on the host plant .…”
Section: Direct Effects Of Climate Change On Arthropodsmentioning
confidence: 91%
“…On the one hand, insects using CO 2 to detect their food source or oviposition site (such as moths, fruit flies or hematophagous insects) can be directly affected . On the other hand, as described before, altered leaf chemistry and temperature can affect second and higher trophic levels in all possible ways . For instance, in aphids, even a single clone has been reported to display different responses to high CO 2 content, depending on the host plant .…”
Section: Direct Effects Of Climate Change On Arthropodsmentioning
confidence: 91%
“…All of these studies have principally focused on parasitoids rather than on predators. Parasitoids, which are considered to be more specialists than predators, seem to be more able to detect the presence of herbivore-induced damage to plants through the perception of secondary metabolites released into the environment by the plant (Holopainen et al 2013). O 3 is more responsible for modifications to plant secondary metabolites and foliar composition than most other greenhouse gases, including CO 2 .…”
Section: Atmospheric Changes Affect Interactions With Natural Enemiesmentioning
confidence: 99%
“…Under elevated CO 2 conditions, the release rates of glucosinolate-derived chemicals is increased (Bidart-Bouzat and Imeh-Nathaniel 2008), which could lead to an enhanced attraction of natural enemies. On the other hand, modifications to the ratios and the dilution of herbivore-induced volatiles due to degradation by air pollutants could disorientate natural enemies (Webster et al 2008, Holopainen et al 2013. Pinto et al (2007a, b) showed that the ability of parasitoid and predator species to locate host plants based on the perception of secondary plant metabolites was minimally affected under elevated O 3 conditions.…”
Section: Atmospheric Changes Affect Tritrophic Chemical Signalingmentioning
confidence: 99%
“…The order of the C6 compound emissions after larval feeding activity may explain at least partially why Cotesia vestalis , a parasitoid of Plutella xylostella , prefers landing on damaged Brassica leaf tissue and first actively analyze the extension of damage, although the host larvae are available on the same leaf (Holopainen et al ). It is likely that emission of hexenal compounds from a damaged area may indicate the most recent damage and presence of host larvae nearby, while emissions dominated by ( Z )‐3‐hexenol and ( Z )‐3‐hexenyl acetate indicate damaged leaf, but not so fresh damage, thus possibly telling the parasitoid about lower probability to find a host larva.…”
Section: Release Of the Voc Signals From Plantmentioning
confidence: 99%